2022
DOI: 10.1038/s42003-022-03768-0
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal truncation modulates α-Synuclein’s cytotoxicity and aggregation by promoting the interactions with membrane and chaperone

Abstract: Abstractα-Synuclein (α-syn) is the main protein component of Lewy bodies, the major pathological hallmarks of Parkinson’s disease (PD). C-terminally truncated α-syn is found in the brain of PD patients, reduces cell viability and tends to form fibrils. Nevertheless, little is known about the mechanisms underlying the role of C-terminal truncation on the cytotoxicity and aggregation of α-syn. Here, we use nuclear magnetic resonance spectroscopy to show that the truncation alters α-syn conformation, resulting in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 98 publications
3
24
0
Order By: Relevance
“…Reduced activity of protein degradation systems, such as proteasomes, autophagic systems and lysosomes occur in patients with synucleinopathies. Therefore, the activation of autophagy gives hope for future therapeutic applications [ 36 , 79 , 82 , 83 ]. There are approaches that are not aimed at α-synuclein in a straight line but affect it indirectly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced activity of protein degradation systems, such as proteasomes, autophagic systems and lysosomes occur in patients with synucleinopathies. Therefore, the activation of autophagy gives hope for future therapeutic applications [ 36 , 79 , 82 , 83 ]. There are approaches that are not aimed at α-synuclein in a straight line but affect it indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is critically related to the anomalous accumulation of α-synuclein, and defects in lysosome-related transmembrane ATP transport enzyme ATP13A2 (also known as PARK9) impair lysosomal function and inhibit the toxicity of α-synuclein. Therefore, this enzyme may be considered a possible target in synucleinopathies [ 36 , 62 ]. Other autophagy activation methods also give hope for future therapeutic applications [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, polyanionic factors such as heparin are particularly effective, but at the same time, specific but unknown phosphorylation modes are required [ 64 , 89 ]. LLPS without heparin and heparin-induced fibrosis depend on the temperature and ionic strength of K18 solution similarly, while heparin-induced K18 fibrosis can form amyloid more efficiently at alkaline pH [ 73 , 90 ]. Recent work also showed that following incubation with PEG, the prolonged LLPS of tau leads to the adoption of known pathogenic conformations of tau, such as oligomers and N-terminal exposure.…”
Section: Llps Promotes Pdd-related Protein Aggregationmentioning
confidence: 99%
“…Also, long-range interactions between the N- and C-terminal regions in monomeric α-synuclein have been shown to stabilize its native compact conformations, both experimentally and computationally . As a consequence, diverse forms of truncated α-synucleins have been studied in relation to Parkinson’s disease. Remarkably, it has been recently proposed that the C-terminal region of α-synuclein balances the interactions between the N-terminal and the membrane, while its truncation facilitates membrane binding . Such results have implications in the cytotoxicity and aggregation of α-synuclein, specifically for the relation of C-terminal truncation to the pathogenesis of Parkinson’s disease …”
Section: Introductionmentioning
confidence: 99%